Algal organic matter and dissolved Mn cooperatively accelerate 17α-ethinylestradiol photodegradation: Role of photogenerated reactive Mn(III). (1st June 2023) - Liao, Zhicheng; He, Huan; Cui, Danni; Cui, Jingye; Yang, Xiaoxia; Guo, Ziwei; Chen, Hao; Dao, Guohua; Huang, Bin; Sun, Hongwen; Pan, Xuejun
Highlights: Mn(II) accelerated EE2 photodegradation in the presence of EOM. Generation of Mn(III) in Mn(II) and EOM mixtures was mainly attributed to O2 − . Possible photodegradation pathways of EE2 mediated by Mn(II) and EOM were proposed. NO3 − promoted Mn(II) oxidation and EE2 photodegradation in eutrophic water. Abstract: Algal extracellular organic matter (EOM), a major fraction of the dissolved organic matter found in eutrophic plateau lakes, can act as a photosensitizer to drive the abiotic oxidation of Mn(II). This process has the potential to generate reactive Mn(III) and influence the fate of organic pollutants. In this study, the photodegradation of 17α-ethinylestradiol (EE2) in the presence of Mn(II) and EOM was investigated with emphasis on the photogeneration mechanism of Mn(III). The results indicated that Mn(II) can accelerate EE2 photodegradation in EOM solution owing to the photogeneration of reactive Mn(III), and the enhancement was greater at higher Mn(II) concentrations. The generation of reactive Mn(III) was mainly attributable to the action of superoxide radical generated by photosensitization of EOM. In addition, the photodegradation of EE2 was slower at higher pH, possibly because of the deactivation of Mn(III) under alkaline conditions. Single-electron transfer was an indispensable process in the photodegradation. The differences in fluorophore content, pH, and NO3 − concentrations are all important determinants for EE2 photodegradation in natural waters. The information obtained in this research would contribute to the understanding of reactions between Mn(II) and EOM, and provide new insights into the behaviors of reactive Mn(III) in eutrophic water irradiated by sunlight. Graphical Abstract: Image, graphical abstract